Enhancing Communication and Life Skills in Veterinary Students : Curriculum Development and Assessment of Methods (PP7-340). - Mills, Jennifer N.; Baguley, John; Coleman, Glen; Meehan, Michael (Australian Learning and Teaching Council (ALTC), 2009)
New veterinary graduates identify 'communication skills' as lacking in their education, but also recognise them as crucial to overall success in veterinary professional life. As interpersonal communication is closely linked to an individual's sense of identity and levels of confidence, an approach taken to improve it requires an understanding of emotional intelligence. This is a report from a collaborative study that sought to inform the emerging veterinary communication curriculum through developing clinical consultations using simulated client scenarios; addressing the human-animal bond; assessing the needs of clients, students and their attitudes to animals; and developing strategies to enhance and report competencies in professional life skills (using e-portfolio). The study found that experiential tasks help first year students identify the importance of communication for success in veterinary life. Client simulations were effectively scaffolded into the curriculum at various levels compatible with students' level of medical knowledge. The study demonstrated a successful method to incorporate training for students to recognise, acknowledge and support the human- animal bond in client consultations. A specific training module was developed and is available on the Bayer Animal Health website.